Simulation Of Neutron Contamination From Medical Linac Using Particle And Heavy Ions Transport Code System (PHITS) - Bilalodin Bilalodin; Aris Haryadi; Bejo Haryanto (Department of Physics, Sebelas Maret University, 2022)
A research on neutron contamination in LINAC device has been carried out using a Monte Carlo method. The simulation is based on the Siemens Primus LINAC machine model whose component consists of target, primary collimator, flattening filter and secondary collimator as its main components. A neutron contamination examination was carried out using a 10 x 10 cm radiation field and a 100 cm SSD. Subsequently, at a distance of 100 cm from the X-ray source, a water phantom is placed. Investigation of the presence of contaminants was carried out the LINAC operating voltages of 6, 8, 10, 15, 18 and 25 MV. The simulation results show that neutron contamination occurs due to the interaction of photons with the components of the LINAC device, namely the primary collimator, flattening filter and secondary collimator. The operating voltages that can produce neutron contaminant start at 10 MV. Increase in the voltage of the LINAC device causes consequent increase in neutron flux. Such increase in neutron flux has the potential to increase therapeutic dose.